The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.fuel.2015.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the kinetics of sulphation of CaO particles under CaL reactor conditions

Abstract: Furthermore it is demonstrated that the number of calcination carbonation cycles changes the sulphation patterns of the CaO from heterogeneous to homogeneous in all the limestones tested. For 50 carbonation calcination cycles and for particle sizes below 200 µm, the sulphation pattern is in all cases homogeneous. The sulphation rates were found to be first order with respect to SO 2 , and zero with respect to CO 2 . Steam was observed to have a positive effect only in the diffusion through the product layer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 65 publications
(84 reference statements)
0
7
1
Order By: Relevance
“…Because the molar volume of CaSO 4 is much larger than that of CaO, the sulfation reaction results in pore blockage along with the product layer development. , Thus, the porous structure parameters are often taken into consideration while analyzing product layer development. Most previous studies examining the product layer focused on the effect of product layer development on the sulfation reaction rather than attrition. Cordero and Alonso reported that the critical product layer thickness corresponding to the kinetic control regime and diffusion control regime changing for limestone sulfation reactions is in the range of 13–43 nm for different types of limestone under varying temperature conditions . Similarly, the reaction of CaO with CO 2 also involves the development of the product layer and the regime change from kinetic control to diffusion control.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Because the molar volume of CaSO 4 is much larger than that of CaO, the sulfation reaction results in pore blockage along with the product layer development. , Thus, the porous structure parameters are often taken into consideration while analyzing product layer development. Most previous studies examining the product layer focused on the effect of product layer development on the sulfation reaction rather than attrition. Cordero and Alonso reported that the critical product layer thickness corresponding to the kinetic control regime and diffusion control regime changing for limestone sulfation reactions is in the range of 13–43 nm for different types of limestone under varying temperature conditions . Similarly, the reaction of CaO with CO 2 also involves the development of the product layer and the regime change from kinetic control to diffusion control.…”
Section: Introductionmentioning
confidence: 89%
“…Many of the attrition studies under fluidized bed conditions, including the present research, are conducted with an attrition time shorter than a few hours, which is much less than that in the study conducted by Xiao et al Therefore, the change in the appearance of the particle as a result of protuberance removal is limited. Meanwhile, the product layer is found to increase continuously as the conversion degree increases . Thus, the attrition rate decrease is thought to be the consequence of the formation of a calcium sulfate product layer, which is harder than calcium oxide. The product layer thickness increases as the conversion degree of sulfation increases, while the attrition rate decreases.…”
Section: Introductionmentioning
confidence: 99%
“…One typical limestone from Shandong Province (denoted as “L”) was chosen as the sorbent precursor for CO 2 capture in the work. It was first milled and sieved by filter screens to get a uniform particle size of <0.2 mm, which was prove to be an efficient size range for CO 2 capture in the literature., , The material then was calcined at 900 °C for 2 h and mixed with coal ash or directly tested in CaL cycles. During calcination, the mass loss is measured to be 41.35%.…”
Section: Methodsmentioning
confidence: 99%
“…The conditions of realization of reaction (5) have been studied sufficiently. Specifically, the reaction is practically applied at temperature (T) 923-1123 K [26][27][28][29][30][31][32] and pressure (P) higher than 3 bar, 28,29 at mole fraction of CO 2 in N 2 (y CO 2 ) higher than 10% [27][28][29][30]33 and at a particle diameter of CaO (d p ) lower than 400 μm. 30,[32][33][34] It must be highlighted that the operating conditions of the reactor of the present work are: T = 550-850 K, y co2 < 10%, d p = 4 mm.…”
Section: The Reactionmentioning
confidence: 99%
“…The conditions of realization of reaction (5) have been studied sufficiently. Specifically, the reaction is practically applied at temperature (T) 923–1123 K and pressure (P) higher than 3 bar, at mole fraction of CO 2 in N 2 (yitalicCO2) higher than 10% and at a particle diameter of CaO (d p ) lower than 400 µm . It must be highlighted that the operating conditions of the reactor of the present work are: T = 550–850 K, y co2 < 10%, d p = 4 mm. The concentration of SO 2 in the pores of CaO particles is constant, due to the fact that there is no effect of gas diffusion in the particle pores. The rate of reaction (1) is defined from the combination of the intrinsic kinetic of reaction (3) and the diffusion of SO 2 in the product layer of CaSO 4 . …”
Section: Introductionmentioning
confidence: 99%